Association of oral health with body weight: a prospective study in community-dwelling older adults - Kiesswetter, Eva; Keijser, Bart J.F.; Volkert, Dorothee; Visser, Marjolein (European Journal of Clinical Nutrition, 2019)
Background: To prevent involuntary weight loss in older people, the knowledge about factors affecting body weight (BW) is essential. Therefore, we aimed to investigate the longitudinal associations of multiple oral health aspects with BW in community-dwelling older adults. Methods: This analysis is based on prospective data with a 10-year follow-up of 657 Dutch community-dwelling older adults (age 66.4 ± 5.8 years, 54% female) from the Longitudinal Aging Study Amsterdam. Participants’ characteristics, BW, and 12 oral health variables (teeth, dentures, nine oral problems, self-rated oral health) were assessed in 2005/07 and 2015/16. The association between oral health and BW was analyzed by mixed models and adjusted for demographic, socio-economic, smoking, health, and functional aspects considering data of both assessments. Results: Mean BW was 79.1 ± 13.3 kg at baseline (B) and 77.6 ± 13.8 kg at follow-up (FU). At baseline, 29.6% of the participants reported being edentulous (FU:34.4%) and 55.8% to wear dentures (FU:62.3%). Dental pain while chewing was the oral problem with the lowest (B:5.2%, FU:6.6%) and xerostomia with the highest prevalence at both examinations (B:24.3%, FU:30.0%). Most participants rated their oral status as healthy (B:65.2%, FU:66.9%). Neither edentulism and denture use nor oral problems showed a longitudinal association with BW. In contrast, self-rated oral health was associated with BW (b = 0.724, SE = 0.296, p = 0.015) after adjusting for multiple confounders. Conclusions: In community-dwelling older adults self-rated oral health may indicate changes in body weight in the long term. Therefore, this simple measure could serve to identify a risk for weight loss and to initiate oral interventions in clinical practice.
CRIS-Team Scopus Importer:2019-12-03